“Også Berlinmuren i den pædagogiske verden står for fald”: En analyse af reformen af pædagoguddannelserne i Danmark 1991 - Sørensen, Astrid Elkjær (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2025)
in may 1991, the danish parliament unanimously adopted an educational reform of the pedagogical area. With the reform, the existing three specialist educational programs were replaced by a common 3 ½-year generalist educational program. This article examines the preparatory work of the reform and the discussion around its content in the committee, the pedagogical trade unions and in the Danish parliament. The reform was characterized by ideas from new public management with a focus on cost-eﬀectiveness and documented skill sets. Thus, the government used the reform to cut spending and solve the shortage of pedagogical staﬀ by introducing paid internship. The trade unions accepted this, as they were given a large say concerning the academic content. However, the trade unions also tried to use the reform to secure a higher status for their profession as well as competencies, which could be recognized in the discourse of new public management. As was characteristic for this period in danish politics, the reform was constructed without any considerations towards gender. as a result important perspectives in the recruitment debate was left untouched.